Mesocycle progression in hypertrophy: Volume versus intensity - Israetel, M.; Feather, J.; Faleiro, T. V.; Juneau, C. E. (Strength and Conditioning Journal, 2020)
Week to week progressions over the course of typically 4-8 weeks (before a recovery week is taken) are one of the central forms of progression in a muscle growth training plan. Should the trainee add more weight to the bar each week, add repetitions to the sets, or add whole sets to provide the best hypertrophy-specific overload? Based on the current literature, the likely answer is "some of all 3," but with a progression in set numbers probably being the most well supported. The trade-offs between repetition and weight progression are not as clear and are discussed.